Revealing the Potential of Compounds in Sappan Wood as Cervical Cancer Metastasis Chemopreventive Agent With MMP9 Target - Hanaan Emilia Adi Hastuti; Midori Rahmadhany Putri Adisusilo; Yusufia Asmarani Ashar; Edy Meiyanto; Riris Istighfari Jenie (Indonesian Journal of Cancer Chemoprevention, 2022)
Matrix metalloproteinase-9 (MMP9) has an essential role in cervical cancer metastasis. Sappan wood extract (SWE) from Caesalpinia sappan contains metabolites that have pharmacological effects and can potentially inhibit metastasis by targeting the protein markers. This research aims to discover the potency of compounds in C. sappan as chemopreventive agents for metastasis in cervical cancer by targeting MMP9. SWE was obtained by maceration with methanol and analyzed using thin layer chromatography (TLC). In vitro cytotoxicity test of SWE on HeLa cells was performed by direct counting method. MMP9 expression profiles and survival rates in cervical cancer patients were explored through bioinformatics studies by the GEPIA database. The CMAUP and PubChem databases were used to obtain the metabolomic profile of SWE. SWE compounds’ activities on target proteins were obtained through KNIME software, while its interaction with MMP9 was analyzed using molecular docking with MOE software. We obtained SWE with a yield of 9.7% w/w. The extract contains brazilin and is indicated by the spot appearance at Rf 0.375. The cytotoxicity of SWE against HeLa cells was considered potential as the IC50 value was 54.93 μg/mL. Based on the bioinformatics analysis, there is a significant difference in MMP9 expression between normal and cervical cancer tissue. The patient’s survival probability decreased if MMP9 was overexpressed. The molecular docking results showed that active compounds of SWE bind to the MMP9 inhibition site with higher affinity compared to the native ligand. This study reveals that SWE potential to be developed as a chemopreventive agent through metastasis inhibition in cervical cancer by targeting MMP9.Keywords: Caesalpinia sappan L., metastasis, bioinformatics, molecular docking, MOE.